The DNA virome varies with human genes and environments - Nolan Kamitaki; David Tang; Steven A. McCarroll; Po-Ru Loh (Nature, 2026)
Abstract Many viruses have adapted to persist in infected humans for life 1,2 . Variable host control of their ongoing abundance (viral load) can lead to clearance or disease 3–5 . Here we analysed the viral DNA load of 31 common viruses in human blood and saliva using whole-genome sequencing data from UK Biobank ( n = 490,401), All of Us ( n = 414,817) and Simons Foundation Powering Autism Research for Knowledge (SPARK; n = 12,519). Viral DNA load varied markedly with age, time of day and season; most viruses were also present at greater abundance in men than in women. Human genetic variation at dozens of loci associated with DNA load of seven viruses: Epstein–Barr virus (EBV, 45 loci), human herpesvirus (HHV)-7 (37 loci), HHV-6B, Merkel cell polyomavirus and three anelloviruses. Variation at the major histocompatibility complex (MHC) locus generated the strongest associations ( P = 5.8 × 10 –9 to 2.5 × 10 –1459 ), which were specific to each virus. The HLA-B*08:01 allele also exhibited a host–virus genetic interaction with EBV subtype ( P = 7.4 × 10 –70 ). Other human genetic effects implicated genes encoding proteins that process peptides for antigen presentation, such as ERAP1 (HHV-7, P = 2.7 × 10 –78 ) and ERAP2 (EBV, P = 4.6 × 10 –111 ). Mendelian randomization analyses supported a strong causal effect of EBV DNA load on increased risk of Hodgkin’s lymphoma ( P = 1.8 × 10 –3 ), but not multiple sclerosis ( P = 0.52). This suggests that higher chronic EBV load increases lymphoma risk, whereas associations of EBV infection with autoimmune conditions reflect host immune responses to particular viral epitopes.